Local anesthetics block induction of the Pseudomonas alk regulon. - Benson, S A (1979)
The local anesthetics procaine and piperocaine blocked induction of the plasmid-determined enzymatic activities involved in the metabolism of n-alkanes in Pseudomonas putida. Procaine reversibly inhibited existing alkane hydroxylase activity. Induction of a soluble aliphatic amidase activity was not affected. These results support the hypothesis that induction of the plasmid-determined alkane metabolic system in P. putida involves a membrane component(s).